2021
DOI: 10.12911/22998993/128874
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Chlorophyll a Phytoplankton in the Coastal Waters of Semarang and Jepara for Monitoring the Eutrophication Process using MODIS-Aqua Imagery and Conventional Methods

Abstract: This study investigates the concentration of chlorophyll-a (chl-a) using the data of field observation and MODIS-Aqua imagery. The field observation data were retrieved by using a conventional method and processed using spectrometric analysis. This study covers the coastal and near land areas which have different levels of anthropogenic activity. The results showed that the coastal waters of Semarang with a high level of anthropogenic activity persistently show a concentration of chlorophyll a (chl-a) twice as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…Based on Jepara Regency Regional Regulation Number 2 of 2011 concerning Jepara Regency Spatial Planning 2011-2031 article 14 paragraph (1-b) states that the plan to build Tanjung Jati coal-fired power plant units 5-6 in Jepara Regency is in accordance with the Jepara spatial plan [17] and this location is not included in the main fishing area for local fishermen [18] The area of the main fishing activity (fishing ground) in an area is strongly influenced by the amount of feed that supports fish life and its ecosystem. The existence of distribution of chlorophyll-a as a source of nutrition which is a source of feed can be an indication of the abundance of fish feed sources [19].…”
Section: Resultsmentioning
confidence: 99%
“…Based on Jepara Regency Regional Regulation Number 2 of 2011 concerning Jepara Regency Spatial Planning 2011-2031 article 14 paragraph (1-b) states that the plan to build Tanjung Jati coal-fired power plant units 5-6 in Jepara Regency is in accordance with the Jepara spatial plan [17] and this location is not included in the main fishing area for local fishermen [18] The area of the main fishing activity (fishing ground) in an area is strongly influenced by the amount of feed that supports fish life and its ecosystem. The existence of distribution of chlorophyll-a as a source of nutrition which is a source of feed can be an indication of the abundance of fish feed sources [19].…”
Section: Resultsmentioning
confidence: 99%
“…Fosfor di perairan dapat berupa partikel anorganik, contohnya dalam bentuk mineral. Fosfat dapat ditemukan dalam bentuk terlarut dan terdeposisi ke dalam pori sedimen melalui proses adsorpsi (Maslukah et al, 2021(Maslukah et al, , 2022. Fosfat memegang peranan penting dalam mengubah energi dalam proses fotosintesis yang dilakukan oleh fitoplankton.…”
Section: Pendahuluanunclassified
“…Namun yang langsung mempengaruhi pertumbuhan fitoplankton (klorofil-a) adalah dalam bentuk anorganik terlarut, yaitu dalam bentuk ion fosfat. Hal ini dikatakan pula oleh Sutamihardja et al (2018), serta Maslukah et al, (2020Maslukah et al, ( , 2021Maslukah et al, ( , 2022 bahwa nilai fosfat yang mengalami peningkatan disebabkan oleh badan air yang menerima masukan beban pencemar dan kemudian terakumulasi, salah satunya adalah dari limbah domestik. Kadar fosfat dalam suatu badan perairan dapat mengalami penurunan ketika kondisi pasang yang disebabkan oleh faktor arus dan pasang surut.…”
Section: Hasil Dan Pembahasanunclassified
“…Determination of the chlorophyll-a concentration in water analysis could be done by field measurements, laboratory measurements, or by monitoring the color of the sea using remote sensing data (Wang et al, 2017;Abbas et al, 2019;Maslukah et al, 2021). One of the remote sensing methods that have been developed to monitor the optical properties of water is using the Sentinel 3 satellite.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite images MODIS and Landsat are also frequently used for chlorophyll-a monitoring. On the north coast of Java, research on chlorophylla using MODIS and Landsat has been done by some researchers, including Siregar Meanwhile, the results of the research by Maslukah et al, (2021) in Semarang waters indicated that the use of MODIS level 3 was not appropriate for monitoring chlorophyll-a in coastal areas or river estuaries. This is related to low spatial resolution (that is 4 km).…”
Section: Introductionmentioning
confidence: 99%